2009
DOI: 10.1088/0957-0233/20/5/055201
|View full text |Cite
|
Sign up to set email alerts
|

Mass sensitivity analysis and designing of surface acoustic wave resonators for chemical sensors

Abstract: The sensitivity of surface acoustic wave (SAW) chemical sensors depends on several factors such as the frequency and phase point of SAW device operation, sensitivity of the SAW velocity to surface mass loading, sensitivity of the SAW oscillator resonance to the loop phase shift, film thickness and oscillator electronics. This paper analyzes the influence of the phase point of operation in SAW oscillator sensors based on two-port resonator devices. It is found that the mass sensitivity will be enhanced if the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A detailed analysis of mass sensitivity of a two-port SAW resonator based oscillator sensor by exploring the implicit dependencies of the loop phase condition have been presented in [7]. By defining S y z = y −1 ∂y/∂z to represent the sensitivity of y with respect to changes in z, it was shown that the frequency sensitivity due to surface mass loading may be represented by [7] S ω…”
Section: A Theoretical Analysis Of Sensitivity Of the Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed analysis of mass sensitivity of a two-port SAW resonator based oscillator sensor by exploring the implicit dependencies of the loop phase condition have been presented in [7]. By defining S y z = y −1 ∂y/∂z to represent the sensitivity of y with respect to changes in z, it was shown that the frequency sensitivity due to surface mass loading may be represented by [7] S ω…”
Section: A Theoretical Analysis Of Sensitivity Of the Sensormentioning
confidence: 99%
“…By defining S y z = y −1 ∂y/∂z to represent the sensitivity of y with respect to changes in z, it was shown that the frequency sensitivity due to surface mass loading may be represented by [7] S ω…”
Section: A Theoretical Analysis Of Sensitivity Of the Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The SAW based microsensor is very promising for the dirt retention on-line monitoring owing to its very excellent mass sensitivity [1][2][3][4] . This paper develops a novel SAW sensor on ST-X quartz substrate with excellent long-term frequency stability for online monitoring towards the dirt retention on the surfaces of the optical lenses.…”
Section: Introductionmentioning
confidence: 99%
“…The gravimetric sensors based on surface acoustic wave (SAW) platform are perhaps the most sensitive, miniature and rugged of them all 12 . Most interesting aspects of SAW sensors are their continuous upgradability in performance through increase in operation frequency 13 , modification in device design [14][15][16][17] , improvement in polymer interface 18 , and planar technology 19 . The SAW sensor technology has gone through development of nearly three decades and still there remains vast potential to exploit [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%